Assessment mindset: Exploring the relationship between teacher mindset and approaches to classroom assessment. (June 2019) - DeLuca, Christopher; Coombs, Andrew; LaPointe-McEwan, Danielle
Highlights: Teacher candidates with a growth mindset prioritized assessment as learning and a differentiated approach to assessment fairness. Teacher candidates with a mixed mindset prioritized assessment for learning and an equitable approach to assessment fairness. Teacher candidates did not hold a fixed mindset. Teacher educators should consider and address teacher candidates' mindsets when teaching about student assessment. Abstract: While previous research has identified the significant influence of teachers' approaches to assessment on student learning, few studies have empirically explored why teachers approach assessment in particular ways. The purpose of this study was to explore the relationship between teacher candidates' approaches to assessment and their mindset towards learning at the end of their teacher education. Data were collected from 396 teacher candidates through the Approaches to Classroom Assessment Inventory and Dweck's Theories of Intelligence Inventory. Significant trends between mindset and teachers' approaches to assessment were observed, specifically, in regards to teacher candidates' mindset and approaches to assessment purpose and fairness. This paper provides empirical evidence that mindset is a component of teacher assessment literacy and argues that assessment mindset involves the specific linkage between teachers' mindsets toward learning and their approach to assessment.